Compatibility tests between Solar Salt and thermal storage ceramics from inorganic industrial wastes. (1st October 2015) - Motte, Fabrice; Falcoz, Quentin; Veron, Emmanuel; Py, Xavier
Highlights: ESEM and XRD characterizations have been performed. Compatibility of these ceramics with the conventional binary Solar Salt is tested at 500 °C. Tested ceramics have relevant properties to store thermal energy up to 1000 °C. Feasibility of using ceramics as filler materials in thermocline is demonstrated. Abstract: This paper demonstrates the feasibility of using several post-industrial ceramics as filler materials in a direct thermocline storage configuration. The tested ceramics, coming from several industrial processes (asbestos containing waste treatment, coal fired power plants or metallurgic furnaces) demonstrate relevant properties to store thermal energy by sensible heat up to 1000 °C. Thus, they represent at low-cost a promising, efficient and sustainable approach for thermal energy storage. In the present study, the thermo-chemical compatibility of these ceramics with the conventional binary Solar Salt is tested at medium temperature (500 °C) under steady state. In order to determine the feasibility of using such ceramics as filler material, Environmental Scanning Electron Microscopy (ESEM) and X-Ray Diffraction (XRD) characterizations have been performed to check for their chemical and structural evolution during corrosion tests. The final objective is to develop a molten salt thermocline direct storage system using low-cost shaped ceramic as structured filler material. Most of the tested ceramics present an excellent corrosion resistance in molten Solar Salt and should significantly decrease the current cost of concentrated solar thermal energy storage system.